The Influence of Service and Product Quality Through Customer Satisfaction on Customer Loyalty of Pt Bank Mandiri, Tbk. Tanjung Balai Sub-Branch Office - Handayani, Mas; Aisyah, Nur; Suryani, Wan; Junita, Audia (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to determine the influence of service and product quality on customer loyalty through customer satisfaction at PT Bank Mandiri, Tbk.Tanjung Balai Sub-Branch Office. This research is quantitative empirical research using hypothesis research which tests the significant influence and direction of direct relationships and indirect relationships between independent variables and dependent variables through intervening variables. This research used a purposive sampling technique which is part of the non-probability sampling technique. The sample of 100 people was obtained from a population of 20,088 by taking samples using the Slovin formula. The data used in this research is primary data obtained directly from the sample through a questionnaire and measured using a Likert scale. Based on the results of statistical tests using the Smartpls application, it was found that service quality does not directly have a significant effect on customer loyalty, while the product quality of Livin Mandiri has a significant effect. Indirectly, service quality does not affect customer loyalty through customer satisfaction. Indirectly, the product quality of Livin Mandiri has an impact on customer loyalty through customer satisfaction.